Pathology and therapeutics for pharmacists : a basis for clinical pharmacy practice / Russell J Greene, Norman D Harris - Greene, Russell J
Aims to show the rationale and role of drug therapy in the management of some common diseases through a consideration of the mechanisms of disease processes in relation to normal function.